The diversity of the orthoreoviruses: Molecular taxonomy and phylogentic divides - Day, J. Michael (Infection, genetics and evolution, 2009)
The family Reoviridae is a diverse group of viruses with double-stranded RNA genomes contained within icosahedral, non-enveloped, double-layered protein capsids. Within the Reoviridae, the Orthoreovirus genus includes viruses that infect reptiles, birds and mammals (including humans). Recent sequencing efforts have produced a great deal of new molecular data for the fusogenic orthoreoviruses, a group of reoviruses that induce cell–cell fusion during an infection. This new data has allowed a fresh look at the phylogenetic relationships among the members of the Orthoreovirus genus, and has provided insight into the evolution of orthoreovirus species and species groups. This review mainly focuses on the molecular taxonomy of the fusogenic orthoreoviruses, and aims to provide insight into their relationships with the non-fusogenic orthoreoviruses and other selected Reoviridae genera.